Differential Communication and Local Information Advantage: Revelations from Translation Differences - Lang, Tina; Stice-Lawrence, Lorien; Wong, Yu Ting Forester; Wong, T. J. (The Accounting Review, 2026)
ABSTRACT We develop an empirical proxy for companies’ differential communication to local and foreign investors using translation differences in public disclosure. We validate our proxy using a field experiment and then use this proxy to document that differential communication is associated with increases in information asymmetry between local and foreign investors. It is also linked to decreases in the relative information quality of foreign analysts, even when foreign demand for information is high and communication costs are low. These and a variety of supporting tests, including those using an alternative artificial intelligence (AI)-based measure of translation differences, suggest that firms engage in differential communication because of a preference for local investors and when responding to incentives to maximize stock price. This study highlights the role of differential communication as one driver of local information advantage in our setting. Data Availability: Most data are available from publicly available sources, as described in the paper. The field experiment data are available upon request. JEL Classifications: G15; G14; M40; M41; G30.